Kelayakan Modul Pembelajaran IPS Berbasis Saintifik Melalui Metode EIATH Kelas IV SD/MI - Rikotul Kolbiyah; Salati Asmahasanah; Muhammad Fahri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The purpose of this research is to find out the steps of module development and feasibility of scientific-based IPS learning modules with EITH (Everyone Is A Theacher Here) method of grade 4 elementary school students. This research uses development research to develop scientific-based learning modules with EITH (Everyone Is A Theacher Here) method in ips subjects based in MI Yapendi Bogor. The results that will be obtained from this study are qualitative and quantitative data. The result of validation and trial results is a number that will later be described. Material validation result score 93%, language validation result 84.61%, design validation result 82.29% of the overall maximum score 100%. The eligibility results of the learning module are declared valid, if the learning module is eligible with a score of 81% - 100% of all elements contained in the questionnaire.